Quarterlife Crisiss Pada Masa Dewasa Awal - Ayqina Mafazania; Hanum Syifa Rafsanjani; Jasmine Mutiara Bintang; Juwita Putri Ananta (BADAN PENERBIT STIEPARI PRESS, 2024)
Quarter-life crisis is a real time that people experience in early adulthood, especially in their 20s and 30s. This crisis is characterized by challenges, fear, confusion and uncertainty about the direction of life and career that individuals face. This crisis often occurs in people who are searching for self-identity and starting a professional career. This study uses library research from various sources such as journals, books, articles and other sources of information found in documents. Information sources can be searched using search engines such as Google Scholar, Scopus and PubMed